Different Approaches for Mesenchymal Stromal Cells Isolation from Wharton’s Jelly Tissue - Oberemok, Ruslana; Trufanova, Natalia; Trufanov, Oleh; Revenko, Olena; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4): 294